Treatment of Kynol fiber materials – Part 2: antistatic and water-repellent functionalization - Juan Wang; Boris Mahltig (Communications in Development and Assembling of Textile Products, 2022)
Kynol fibers are flame retardant high performance fibers. Without further treatment they do not exhibit significant antistatic or water-repellent properties. With this background, several conventional antistatic agents and one hydrophobic finishing agent are evaluated to introduce these properties to Kynol fiber materials. Also, the combination of both properties is investigated to realize bifunctional fiber materials. By application of antistatic finishing agents, the electric surface resistance of Kynol fiber materials can be decreased to values smaller 108 W, which is a good value related to antistatic properties. By application of the hydrophobic agent, water repellent properties can be introduced to Kynol fiber materials. However, simultaneously the antistatic properties are decreased. The combination of both types of agents in a kind of bifunctional finishing can lead to intermediate antistatic effects combined with an intermediate water repellency. Nevertheless, in bifunctional application no single excellent property is gained. The flame retardant properties are tested on selected samples after the finishing processes. No change in flame retardant properties is determined, if the finishing agents are applied. For this, the presented results can be the starting point for development of functionalized flame retardant Kynol fiber products.